It is: nth term = 5-4n and so the next term will be -19
If you mean -1 3 7 11 15 then the nth term is 4n-5 and so the next term will be 19
2n+3. If 5 is the first term, then it is 2n + 3 (2×1 = 2 + 3 = 5 and 2×2 + 3 = 7)
Un = (-1)n*(2n - 1)
This is the Fibonacci sequence, where the number is the sum of the two preceding numbers. The nth term is the (n-1)th term added to (n-2)th term
The nth term of the sequence is 2n + 1.
It is: nth term = 5-4n and so the next term will be -19
If you mean -1 3 7 11 15 then the nth term is 4n-5 and so the next term will be 19
Un = 4n - 9
5 first terms in n²+3
The nth term is 4n - 3
12 - 5(n-1)
2n+3. If 5 is the first term, then it is 2n + 3 (2×1 = 2 + 3 = 5 and 2×2 + 3 = 7)
Un = (-1)n*(2n - 1)
This is an arithmetic sequence with initial term a = 3 and common difference d = 2. Using the nth term formula for arithmetic sequences an = a + (n - 1)d we get an = 3 + (n - 1)(2) = 2n - 2 + 3 = 2n + 1.
2n + 1
The given sequence is an arithmetic sequence with a common difference of 4 between each term. To find the nth term of an arithmetic sequence, we use the formula: nth term = a + (n-1)d, where a is the first term, d is the common difference, and n is the term number. In this case, the first term (a) is -3, the common difference (d) is 4, and the term number (n) is the position in the sequence. So, the nth term of the given sequence is -3 + (n-1)4 = 4n - 7.